2010
DOI: 10.1302/0301-620x.92b10.24221
|View full text |Cite
|
Sign up to set email alerts
|

Anteroposterior positioning of the tibial component and its effect on the mechanics of patellofemoral contact

Abstract: The biomechanics of the patellofemoral joint can become disturbed during total knee replacement by alterations induced by the position and shape of the different prosthetic components. The role of the patella and femoral trochlea has been well studied. We have examined the effect of anterior or posterior positioning of the tibial component on the mechanisms of patellofemoral contact in total knee replacement. The hypothesis was that placing the tibial component more posteriorly would reduce patellofemoral cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 16 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…Another advantage of our study is the use of a detailed MMBS model incorporating relevant muscles of the lower extremity as active force elements compared to previous studies that assumed the muscles to apply only constant forces [15,16,30,51,85], considered only few muscles [28,33], or analyzed passive load cases without active muscle forces [34]. Our study showed the potential of MMBS in very comprehensively investigating the effects of surgical parameters on knee joint dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage of our study is the use of a detailed MMBS model incorporating relevant muscles of the lower extremity as active force elements compared to previous studies that assumed the muscles to apply only constant forces [15,16,30,51,85], considered only few muscles [28,33], or analyzed passive load cases without active muscle forces [34]. Our study showed the potential of MMBS in very comprehensively investigating the effects of surgical parameters on knee joint dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…However, most experimental studies have only investigated passive knee flexion without active muscle forces, simulated rather uncommon motion patterns, commonly the knee rig configuration [28,33,42,51], or assumed a static quadriceps force, usually some predefined maximum value [28]. Furthermore, only a few studies addressing the biomechanical impact of different patellar component positions and designs on PF dynamics could be identified [15,18,28,33].…”
Section: Introductionmentioning
confidence: 99%
“…The changes in shape, dimensions and positioning may have affected AP alignment of the tibial tray. A more anterior position leads to increased stress on the patellofemoral joint and less efficient use of the extensor mechanism [19]. …”
Section: Discussionmentioning
confidence: 99%
“…The pressure within the PFJ following TKA is a strong indicator of the risk of wear of the implanted patella button and pain within the joint. 9,57,58 Previous studies have used the Pliance system 14,18 or the K-Scan and I-Scan systems (Tekscan, Boston, MA, USA) 17,19,59 to measure contact area and pressure dynamically within the PFJ. However, these were not suitable for use in this study due to the low sensor density and relatively large thickness (2 mm) of the Pliance sensor, and the limited pliability and high expense of the Tekscan systems.…”
Section: Discussionmentioning
confidence: 99%